Identification of RAPD Marker Linked to Mungbean Yellow Mosaic Virus Resistance in French Bean (Phaseolus vulgaris L.) - K V Ravishankar (Society for Promotion of Horticulture - Indian Institute of Horticultural Research, 2009)
Mungbean yellow mosaic virus (MYMV) causes yield loss up to 80 % and is becoming problematic in French bean growing areas. Molecular marker linked selection to MYMV resistance is helpful in rapid identification of genotypes carrying resistant genes. Hence, the present study was undertaken to identify the RAPD marker associated with MYMV resistance in French bean (Phaseolus vulgaris L.). Bulk segregant analysis (BSA) was used to identify RAPD marker linked to MYMV resistance. More than 140 random decamers were surveyed for identification of polymorphic markers between the DNA bulks of resistant and susceptible F2 individuals and their contrasting parents. Ninety eight per cent of these primers amplified DNA in both parents and bulks. Twenty two primers produced specific bands for resistant parent which was absent in the susceptible parent. Out of 22 primers, four primers produced specific fragments viz., OPG 13458, OPX 5670, OPW 17380 and OPP 07730, respectively in resistant parent and bulk, which were absent in susceptible parent and bulk. Amplification of individual DNA samples of segregating F2 resistant individuals using putative marker, OPP 07730, a decamer revealed polymorphism in all four resistant and four susceptible F2 segregants, indicating that the marker OPP 07730 was associated with MYMV resistance in IC-525260, a resistant genotype.